The impact of job rotation on employees’ performance A case study: Utrak Financial Services Limited - Adjei, Dora (2015)
A thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master in Business Administration.